DES of the turbulent flow around a circular cylinder of finite height - Elbatran, Aly Hassan (Journal of Naval Architecture and Marine Engineering, 2016)
The current research work investigates numerically the turbulent flow field characteristics around three dimensional circular cylinder of finite height at Reynolds number of 43000 using Detached Eddy Simulation (DES) turbulence model. Comparison of the numerical results with the experiment data has been taken place. The results reveals that the DES turbulence model is superior for predicting the flow past the circular cylinder of finite height at this Re. The numerical results of this study show the great potential of the presented DES for investigating the complicated flow structure in this case. DES is very accurate for predicting the flow characteristics in many sophisticated cases and can reduce the computational efforts during the simulation process in comparison with Large Eddy Simulation (LES) turbulence mathematical model.